2010
DOI: 10.1074/jbc.m110.118349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Class I P450 Electron Transfer System from Novosphingobium aromaticivorans DSM12444

Abstract: Cytochrome P450 (CYP) 4 enzymes constitute a superfamily of heme-containing monooxygenases (1, 2) that participate in a variety of biological processes such as carbon source assimilation, biosynthesis and biodegradation, xenobiotic detoxification, and metabolism of medicines (1, 2). The most common activity of P450 enzymes is the insertion of an oxygen atom from dioxygen into chemically inert carbon-hydrogen bonds, but other reaction types including dealkylation, desaturation, heteroatom oxidation, epoxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
135
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(148 citation statements)
references
References 72 publications
13
135
0
Order By: Relevance
“…We also included CYP101D1 (PDB ID code 4C9K) (17) as a control. CYP101D1 is a very close homolog to P450cam and uses camphor as a substrate to give the same product as P450cam (16). Comparing CYP101D1 with P450cam provided insights on the range of motion that the substrate can experience, yet retain regioselective and stereoselective hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also included CYP101D1 (PDB ID code 4C9K) (17) as a control. CYP101D1 is a very close homolog to P450cam and uses camphor as a substrate to give the same product as P450cam (16). Comparing CYP101D1 with P450cam provided insights on the range of motion that the substrate can experience, yet retain regioselective and stereoselective hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…We also carried out a control simulation with another P450, CYP101D1. CYP101D1 is a very close homolog to P450cam, with an rms deviation of 1.0 Å for backbone atoms and has a very similar active site structure (16). CYP101D1 catalyzes exactly the same reaction as P450cam at the same rate giving the same single product (16).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The first electron transfer is rate limiting for a number of bacterial P450 systems including P450 cam (CYP101A1) from Pseudomonas putida (Brewer and Peterson, 1988), CYP199A2 and CYP199A4 from Rhodopseudomonas palustris (Bell et al, 2010b(Bell et al, , 2010c) and CYP101D1 from Novosphingobium aromaticivorans Bell et al, 2010a;Yang et al, 2010). It has been shown that the first flavin-to-heme electron transfer, though one of the slower steps in the overall catalytic cycle, is not rate limiting for palmitate and arachidonate oxidation by P450 BM3 (Munro et al, 1996;Ost et al, 2003;Whitehouse et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They can catalyze reactions of oxidation, reduction or oxidative breakdown of xenobiotics ( Figure 2). It seems that they are evolutively conserved since genomes from virus, bacteria, algae, plant, fungi and animals have isoforms of CYP codified (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In eukaryotic organisms, CYP is found in smooth endoplasmic reticulum, and can biotransform a wide range of pollutants.…”
Section: Cytochrome P450 (Cyp)mentioning
confidence: 99%